UJI POTENSI EKSTRAK DAUN KETEPENG CINA ( Cassia alata L.) TERHADAP PENGHAMBATAN PERTUMBUHAN Trichophyton sp - Noor Hujjatusnaini (El-QUDWAH, 2007)
Trichophyton sp is a phaetogenic microscopic fungi which can cause infection on the outside part of our skin or skin surface and make skin disease or in medical term known as ”dermatomikosis” such as white bloches or ringworm. While Cassia Alata L. is a leaf which used by some people as a material for hose skin diseases traditionally. The purpose of this research is to know the effect of Cassia Alata on the growth of Trichophyton sp, through the treatment to its extract consentration  in order to know its effective concentration level in prevent the growth of Tricophyton sp. The result of this research shows that the concentration of  Cassia alata L. exctract has a very significant affect ti the growth of Trichophyton sp within 1 x 24 hours, 2 x 24 hours, while in 3 x 24 hours and 4 x 24 hours its affect was not significantly different to the growth of Trichophyton sp.